Carbohydrate utilization by the gut microbiome determines host health responsiveness to whole grain type and processing methods. (31st December 2022) - Smith, Caroline; Van Haute, Mallory J.; Xian, Yibo; Segura Munoz, Rafael R.; Liu, Sujun; Schmaltz, Robert J.; Ramer-Tait, Amanda E.; Rose, Devin J.
ABSTRACT: Little is known about how interactions among grain processing, grain type, and carbohydrate utilization (CU) by the microbiome influence the health benefits of whole grains. Therefore, two whole grains – brown rice and whole wheat – and two processing methods – boiling (porridge) and extrusion – were studied for their effects on host metabolic outcomes in mice harboring human microbiomes previously shown in vitro to have high or low CU. Mice carrying either microbiome experienced increases in body weight and glycemia when consuming Western diets supplemented with extruded grains versus porridge. However, mice with the high but not low CU microbiome also gained more weight and fat over time and were less glucose tolerant when consuming extruded grain diets. In high CU microbiome mice, the exacerbated negative health outcomes associated with extrusion were related to altered abundances of Lachnospiraceae and Ruminococcaceae as well as elevated sugar degradation and colonic acetate production. The amplicon sequence variants (ASVs) associated with extruded and porridge diets in this in vivo study were not the same as those identified in our prior in vitro study; however, the predicted functions were highly correlated. In conclusion, mice harboring both high and low CU microbiomes responded to the whole grain diets similarly, except the high CU microbiome mice exhibited exacerbated effects due to excessive acetate production, indicating that CU by the microbiome is linked to host metabolic health outcomes. Our work demonstrates that a greater understanding of food processing effects on the microbiome is necessary for developing foods that promote rather than diminish host health. Abbreviations : CU- carbohydrate utilization; SCFA- short-chain fatty acids; GF- germ-free; HMA, human-microbiome associated; ipGTT- intraperitoneal glucose tolerance test; HOMA-IR- Homeostatic Model Assessment for Insulin Resistance; AUC- area under the glycemia curve; ASV- amplicon sequence variant; lf- low-fat; wd- Western diet; wd_wwp- Western diet containing whole wheat porridge; wd_wwe- Western diet containing whole wheat extrudate; wd_bre- Western diet containing brown rice extrudate; wd_extr- Western diet containing either whole wheat or brown rice extrudate.